High-intensity Exercise in Men with Type 1 Diabetes and Mode of Insulin Therapy - Gawrecki, Andrzej; Naskret, Dariusz; Niedzwiecki, Pawel; Duda-Sobczak, Anna; Araszkiewicz, Aleksandra; Zozulinska-Ziolkiewicz, Dorota (International Journal of Sports Medicine, 2017)
The purpose of this study was to evaluate the impact of high intensity exercise on glucose levels and risk of metabolic decompensation in males with type 1 diabetes (T1D), depending on the method of insulin administration. The study comprised 29 males (aged 25.3±5.1 years; duration of diabetes 10.3±3.2 years) treated with continuous subcutaneous insulin infusion (CSII) or multiple daily insulin injections (MDI). Treadmill exercise test was performed twice in each patient until subjective exhaustion as maximum according to the Borg scale. All the patients achieved ≥85% of the maximal heart rate. Distance during the test was 4 500±1 400 m and 4 473±1 559 m in the MDI and CSII groups, respectively, which was achieved in 31±8 min. During the test and in the 6 h after, no clinically significant episodes of hypoglycemia occurred. Mean glucose levels did not exceed 10 mmol/L in most patients. The risk of the composite endpoint (hypoglycemia<3.8 mmol/L, hyperglycemia≥16.6 mmol/L, ketones≥0.6 mmol/L, and lactate>2.2 mmol/L) was higher in patients treated with MDI than CSII (OR3.75, 95%CI:1.22–11.52, p=0.02). In conclusion, planned high intensity physical effort in men with well-controlled T1D is metabolically safe. CSII shows greater metabolic advantage over MDI during and after high intensity exercise in men with T1D.
Keywords: type 1 diabetes; high intensity exercise; metabolic decompensation; hypoglycemia; continuous subcutaneous insulin infusion; multiple daily injections